2007
DOI: 10.1152/ajprenal.00389.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen peroxide on ROMK channels in the cortical collecting duct

Abstract: We used the patch-clamp technique to study the effect of H2O2 on the apical ROMK-like small-conductance K (SK) channel in the cortical collecting duct (CCD). The addition of H2O2 decreased the activity of the SK channels and the inhibitory effect of H2O2 was larger in the CCD from rats on a K-deficient diet than that from rats on a normal-K or a high-K diet. However, application of H2O2 did not inhibit the SK channels in inside-out patches. This suggests that the H2O2-mediated inhibition of SK channels was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…We and others have shown that the K restriction decreased ROMK channel activity and caused the internalization of ROMK channels. 13,26,27 Although the molecular mechanism by which low K suppresses ROMK channel activity and renal K secretion is not completely understood, our previous study suggests that superoxide anions and related products are signaling molecules that mediate the effect of low K intake on ROMK channels and renal K secretion 4,7,28 Furthermore, we show that P38 and ERK MAPK and PTK are involved in mediating the effect of superoxide anions on ROMK channels. 4,7,28 The role of P38 and ERK MAPK in mediating the effect of low K intake and superoxide anions on ROMK channels is supported by several lines of evidence: (1) Application of hydrogen peroxide stimulated the phosphorylation of ERK and P38 MAPK in M-1 cells; (2) inhibition of superoxide anion production with tempol abolished the stimulatory effect of low K intake on the phosphorylation of P38 and ERK; and (3) suppression of P38 and ERK MAPK increased ROMK channel activity and diminished the inhibition of ROMK channels induced by hydrogen peroxide in the CCD.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…We and others have shown that the K restriction decreased ROMK channel activity and caused the internalization of ROMK channels. 13,26,27 Although the molecular mechanism by which low K suppresses ROMK channel activity and renal K secretion is not completely understood, our previous study suggests that superoxide anions and related products are signaling molecules that mediate the effect of low K intake on ROMK channels and renal K secretion 4,7,28 Furthermore, we show that P38 and ERK MAPK and PTK are involved in mediating the effect of superoxide anions on ROMK channels. 4,7,28 The role of P38 and ERK MAPK in mediating the effect of low K intake and superoxide anions on ROMK channels is supported by several lines of evidence: (1) Application of hydrogen peroxide stimulated the phosphorylation of ERK and P38 MAPK in M-1 cells; (2) inhibition of superoxide anion production with tempol abolished the stimulatory effect of low K intake on the phosphorylation of P38 and ERK; and (3) suppression of P38 and ERK MAPK increased ROMK channel activity and diminished the inhibition of ROMK channels induced by hydrogen peroxide in the CCD.…”
Section: Discussionmentioning
confidence: 65%
“…13,26,27 Although the molecular mechanism by which low K suppresses ROMK channel activity and renal K secretion is not completely understood, our previous study suggests that superoxide anions and related products are signaling molecules that mediate the effect of low K intake on ROMK channels and renal K secretion 4,7,28 Furthermore, we show that P38 and ERK MAPK and PTK are involved in mediating the effect of superoxide anions on ROMK channels. 4,7,28 The role of P38 and ERK MAPK in mediating the effect of low K intake and superoxide anions on ROMK channels is supported by several lines of evidence: (1) Application of hydrogen peroxide stimulated the phosphorylation of ERK and P38 MAPK in M-1 cells; (2) inhibition of superoxide anion production with tempol abolished the stimulatory effect of low K intake on the phosphorylation of P38 and ERK; and (3) suppression of P38 and ERK MAPK increased ROMK channel activity and diminished the inhibition of ROMK channels induced by hydrogen peroxide in the CCD. 28 The evidence to support the role of PTK in mediating the effect of low K intake and superoxide anions on ROMK channel activity 26 includes the following: (1) Low K intake significantly increased the expression of Src family PTK and suppression of superoxide anions abolished the effect of low K intake on PTK expression, 4 (2) increased PTK activity enhanced the tyrosine phosphorylation of ROMK channels 29 and enhanced the internalization of ROMK channels, 8 and (3) inhibition of PTK attenuated the hydrogen peroxide-induced inhibition of ROMK channels in the CCD.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In particular, when the channels are closed by low pH on the cytoplasmic side of the patch, recovery is greatly accelerated by addition of a reducing agent such as DTT (30,46 To test this further, we incubated intact tubules with an oxidizing agent, H 2 O 2 , added to the bath. This compound was previously shown to inhibit ROMK channels in cell-attached patches from the CCD (40). TPNQ-sensitive currents were then measured immediately after formation of whole-cell conditions to assess the response of the intact cell to the oxidant.…”
Section: Resultsmentioning
confidence: 99%